Morfoloske i somatotipske karakteristike vrhunskih hrvatskih veslaa - Mikulic, P.; Vucetic, V.; Matkovic, B.; Oreb, G. (Croatian Sports Medicine Journal, 2006)
The aim of this study was to determine some morphological characteristics, to determine the body composition with regard to subcutaneous fat tissue vs. lean body mass ratio, determine the somatotype as well as analyze the differences in the area of morphological characteristics between «A» (age =23) and «B» seniors (age <23). The sample consisted of 29 best Croatian rowers. Body composition was determined by measuring 7 skin fold measurements according to Jackson an Pollock, and according to IBP recommendations the following dimensions were measured: body height and weight, arm reach, leg, arm, fist and foot length, biacromial and bicristal range, diameters of elbow, wrist and knee as well as the girth of leg, arm, fist and foot. Somatotype was determined by Heath & Carter method based on Sheldon's classification. Results indicated that Croatian rowers are significantly heavier and taller than normal population, and similar when compared to other international rowers. Subcutaneous fat tissue is less developed, and girth dimensions are larger than those find in non athletes. That is a result of rowers' specific training as well as voluminosity of rowers' body. Somatotype indicated especially developed mezomorphic component followed by endomorphic component, with ectomorphic component being the least developed. Body height and arm reach were the only dimensions in which the two observed groups of examinees produced statistically significant differences (with«A» seniors achieving larger dimensions).